The development of musculoskeletal radiology for 100 years as presented in the pages of Acta Radiologica. (November 2021) - Geijer, Mats; Inci, Fatih; Solidakis, Nektarios; Szaro, Pawel; Al-Amiry, Bariq
During the last 100 years, musculoskeletal radiology has developed from bone-only radiography performed by everyone to a dedicated subspecialty, still secure in its origins in radiography but having expanded into all modalities of imaging. Like other subspecialties in radiology, it has become heavily dependent on cross-sectional and functional imaging, and musculoskeletal interventions play an important role in tumor diagnosis and treatment and in joint diseases. All these developments are reflected in the pages in Acta Radiologica, as shown in this review.